Az angolszász trónöröklés és Hódító Vilmos trónigénye - Rózsa, Csongor Ernő (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
According to the time-honoured Hungarian historiography the rights of William the Conqueror to the throne were well-founded and he truly came to the island because of the defence of his rights. The English historians and legal historians on the other hand says that the situation is much more nuanced and nowadays they believe that some details of the Bayeux Tapestry has a deeper meaning in accordance with the events of the Conquest. In my essay I am briefly outlining the events before 1066 and the state of the English Kingdom at that time, then I examine from legal historian perspective the Anglo-Saxon succession norms (or the lack of them), lastly I scrutinize the claims of William the Conqueror each one by one. This way – in Hungary – this essay will be the first legal historian work in relation with the claims of the Norman prince.